Effects of different fertilization conditions and different geographical locations on the diversity and composition of the rhizosphere microbiota of Qingke (Hordeum vulgare L.) plants in different growth stages - Wang, Lei; Wang, Handong; Liu, Meijin; Xu, Jinqing; Bian, Haiyan; Chen, Tongrui; You, En; Deng, Chao; Wei, Youhai; Yang, Tianyu; Shen, Yuhu (Frontiers in Microbiology, 2023)
The application of chemical fertilizers can effectively improve soil quality and crop yield. Rhizosphere microbiota, which consist of highly diverse microorganisms, play an important role in soil quality. However, there is limited information about the effects of different fertilization conditions on the growth of Qingke (hull-less barley) plants and composition of the rhizosphere microbiota of the plants. In this study, we characterized the rhizosphere microbiota of Qingke plants grown in three main Qingke-producing areas (Tibet, Qinghai, and Gansu). In each of the three areas, seven different fertilization conditions were applied. The growth and yields of the Qingke plants were compared. The three areas differed in the alpha diversity and beta diversity of the rhizosphere microbiota of Qingke plants. In each area, differences in fertilization conditions and differences in the growth stages of Qingke plants resulted in differences in the beta diversity of the rhizosphere microbiota. At different depths of soil and different growth stages of Qingke plants, there were marked differences in the composition of the rhizosphere microbiota at the phylum and genus levels. For most of microbial pairs established through network analysis, the significance of their correlations in each of the microbial co-occurrence networks of the three Qingke-producing areas was different. Moreover, in each of the three networks, there were significant differences in relative abundance and genera among most nodes. The soil chemical properties (i.e., TN, TP, SOM, AN, AK, CEC, Ca, and K) were positively or negatively correlated with the relative abundance of the top 30 genera derived from the three main Qingke-producing areas. Fertilization conditions markedly influenced the height of a Qingke plant, the number of spikes in a Qingke plant, the number of kernels in a spike, and the fresh weight of a Qingke plant. Collectively, rhizosphere microbiota is essential for the quality of soil and yields of Qingke plants.